IMMOBILIZATION OF Β-GALACTOSIDASE FROM HYPOCREA JECORINA ON HYDROXYAPATIDE AND ALUMINA - Fulya Aytaç Türkan; Ayşegül Peksel (Sabiad)
Objective: β-galactosidase obtained from the Hypocrea jecorina QM9414 mold fungus was immobilized on alumina and hydroxyapatite (HA) using the adsorption method, and the specific activity and protein values of the immobilized enzyme relative to the free enzyme were measured and evaluated. Materials and Methods: Partially purified β-galactosidase enzyme obtained from the mold fungus Hypocrea jecorina QM9414 was physically bound to alumina and hydroxyapatite carriers with the adsorption method. For this, filtering, washing, and drying processes were carried out. A UV-spectrophotometer device was used for the measurements. Results: The results of the adsorption on HA showed the efficiency of the immobilized enzyme to be 88% as specific activity unit (U/mg), while it was 18.6% when calculated considering the protein amounts (mg/ml). As the result of the adsorption on alumina, the efficiency of the immobilized enzyme was found to be 36.8% as specific activity unit (U/mg), while it was 22.4% when calculated considering the protein amounts (mg/ml). Conclusion: It has been shown that β-galactosidase can be efficiently immobilized on biocompatible HA via a very simple immobilization protocol, offering a promising strategy to perform repeated enzymatic hydrolysis reactions. The fact that β-galactosidase, which is partially purified from Hypocrea jecorina QM9414 mold fungus, is immobilized on alumina and hydroxyapatite with the adsorption method, makes our study unique as this is the first time it appears in the literature.